PENGARUH PENGGUNAAN GADGET TERHADAP KETERAMPILAN SOSIAL SISWA KELAS V DI SD NEGRI PASIRPANJANG - Meril Hikmah Priananda (STKIP Subang, 2026)
This study aims to examine the effect of gadget usage on the social skills of fifth grade students at SD Negeri Pasirpanjang. The rapid development of digital technology has increased the accessibility and intensity of gadget use among elementary school students in daily life. Excessive gadget usage is assumed to reduce direct social interaction and influence students’ abilities in communication, cooperation, empathy, and social responsibility. This research employed a quantitative approach using a survey method. The population of this study consisted of all fifth grade students at SD Negeri Pasirpanjang, while the sample was selected through a simple random sampling technique. Data were collected using questionnaires that measured gadget usage intensity and students’ social skills. The data were analyzed using descriptive statistics and inferential statistical analysis to determine the effect of gadget usage on students’ social skills. The results showed that gadget usage had a significant effect on the social skills of fifth grade students at SD Negeri Pasirpanjang. Students with higher gadget usage intensity tended to demonstrate lower levels of social skills, especially in face to face communication and peer interaction. These findings indicate that uncontrolled gadget usage may negatively affect students’ social development at the elementary school level. Therefore, cooperation between teachers and parents is strongly needed to supervise, guide, and control students’ gadget usage. Proper supervision and guidance are expected to help students use gadgets wisely while maintaining healthy social interactions and balanced social development. This study provides practical implications for educational policy and classroom social practice.